The beginner's guide to sourdough : best-kept secrets for successful bread every time - Coyne, Amy (Page Street Publishing Co., 2025)
"A Masterclass in Sourdough. Discard your worries with this ultimate beginner's guide to sourdough baking! Sourdough enthusiast Amy Coyne has harnessed her decade of experience and compiled her best tips, tricks, and customizable baking schedules in this collection of 50 family-friendly recipes. With long-form bakes containing step-by-step photos and QR codes linked to video tutorials, anyone will be able to make sourdough without breaking a sweat. Organized to optimize success, each chapter allows you to master a different element of sourdough: - Kick-start your journey with everything you need to know on starter. - Craft your first sourdough loaves with confidence using approachable bakes like Easy Crusty Sourdough or Soft Rosemary Bread. - Conquer artisanal favorites from Everything Bagel Loaves to Chocolate Cherry Sourdough. - Bake delicious everyday sandwich loaves like Fluffy White Sandwich Bread and Honey Oatmeal Sourdough. - Shape savory showstoppers from Classic Dinner Rolls to Sourdough Garlic Knots. - Master stiff-levain treats like The Best Cinnamon Rolls, Caramel Pecan Monkey Bread, or Raised Sourdough Donuts. - Never let anything go to waste with clever discard recipes. Whether you want to take a crack at your first starter or broaden your bread baking repertoire, Amy has created a one-stop shop for beginning or continuing your sourdough journey."--Amazon.com.